Log horizon : the West Wind Brigade. 4 - Touno, Mamare (Yen Press, 2016)
"Trapped in the game world of Elder Tales, Soujirou and the fetching lasses of the West Wind Brigade are getting tired of the tasteless food. However, with the sudden appearance of a burger joint, it seems the bland monotony may be at an end--but the quest for the secret to tasty burgers is not giong to be as easy as they'd like."--Page [4] of cover.